2013
DOI: 10.1093/pubmed/fds102
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the epidemiology of unintentional burn injuries in South Asia

Abstract: Preventing burns in the household in South Asia, particularly around kitchen activities, is essential. Children in South Asia are susceptible to burns and are an important target population. Future research should focus on filling the gaps in burn epidemiology found in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
68
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 46 publications
14
68
5
1
Order By: Relevance
“…43 It was higher than the other previous literatures from high income countries such as 1.3% in Kuwait, 80 0.7% in America, and 1.1% in Europe, 25 but was less than the result obtained by Golshan, et al in South Asia 9%. 81 An important point is that the burnt patients from other provinces treated or died as outpatients and were excluded. In addition, hospitals mortality rates are likely to be related to the quality of hospital care and case mix in terms of factors associated with mortality.…”
Section: Mortalitymentioning
confidence: 99%
“…43 It was higher than the other previous literatures from high income countries such as 1.3% in Kuwait, 80 0.7% in America, and 1.1% in Europe, 25 but was less than the result obtained by Golshan, et al in South Asia 9%. 81 An important point is that the burnt patients from other provinces treated or died as outpatients and were excluded. In addition, hospitals mortality rates are likely to be related to the quality of hospital care and case mix in terms of factors associated with mortality.…”
Section: Mortalitymentioning
confidence: 99%
“…Globally, scald injuries are an important public health issue and cause considerable morbidity and mortality [1][2][3]. They can be the most distressing and painful injuries a child can receive and may result in long-term physical and psychological effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the majority of scalds in childhood occur at home [1,[4][5][6] and are most commonly caused by hot liquids from kettles, cups and baths [2,[5][6][7][8]. Children under the age of 5 years are most at risk of sustaining a scald in the home [9,10] and the burden of paediatric scalds falls most heavily on those from the most disadvantaged groups [4,5,11,12] Preventing scalds requires understanding of modifiable risk factors for scalds.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the mother died of a burn injury; therefore, it is classified as an injury death rather a maternal death due to maternal complications (12)(13)(14). It was revealed that the mother caught fire in her "saree" during winter season when warming herself by the fire in the courtyard, a known risk factor (15). In India, 50.6% of women who suffered flame burns were found to be wearing traditional saree (15).…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that the mother caught fire in her "saree" during winter season when warming herself by the fire in the courtyard, a known risk factor (15). In India, 50.6% of women who suffered flame burns were found to be wearing traditional saree (15). This case study took place in Bangladesh where seasonal variations in fire-related and burn injuries occur, with winter being the most common season because of exposure of saree or winter cloths to open flame, cooking fire, traditional kerosene lamp, even to heating fire (4).…”
Section: Discussionmentioning
confidence: 99%